PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA MASA PANDEMI COVID-19 DI PT.TELKOM AKSES KEDIRI - Nabela Patu Milena R; Sonny Subroto Maheri Laksono, Lina Saptaria (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Occupational health safety is urgently needed at this time in accordance with the new normal rules of the Covid-19 health protocol, in order to remain productive and economic activities run healthily and safely by prioritizing preventive measures. The purpose of this study was to find out how to apply occupational safety and health in the era of the Covid 19 pandemic at PT. Telkom Access Kediri. This research is qualitative research using interview, observation, and documentation methods. The result is the implementation of the K3 (Occupational Health and Safety) policy in the era of the Covid-19 pandemic at PT. Telkom Access Kediri has in fact been running optimally. PT. Telkom Access Kediri implements a policy of sanctions on employees who violate company regulations, as well as PT. Telkom Access Kediri conducts periodic evaluations on the implementation of K3 policies in all units.